2021
DOI: 10.1007/s11244-021-01494-1
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Self Cleavage Pistol Ribozyme Mechanism

Abstract: Ribozymes are huge complex biological catalysts composed of a combination of RNA and proteins. Nevertheless, there is a reduced number of small ribozymes, the self-cleavage ribozymes, that are formed just by RNA and, apparently, they existed in cells of primitive biological systems. Unveiling the details of these “fossils” enzymes can contribute not only to the understanding of the origins of life but also to the development of new simplified artificial enzymes. A computational study of the reactivity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…[57] This was not the case for the models in which guanine G40 was parametrized as deprotonated at the N1 atom ("reversed protonation"). [58] Interestingly, the G40 variants tested here (c 1 G, c 3 G and X) lose the wavy shape of their rate-pH profiles. They seem to lack cooperative interactions with an influencer, resulting in pK a values in the same range as modelled for the wildtype in absence of an influencer.…”
Section: Apparent Pk a Values From Activity-ph Profilesmentioning
confidence: 77%
See 2 more Smart Citations
“…[57] This was not the case for the models in which guanine G40 was parametrized as deprotonated at the N1 atom ("reversed protonation"). [58] Interestingly, the G40 variants tested here (c 1 G, c 3 G and X) lose the wavy shape of their rate-pH profiles. They seem to lack cooperative interactions with an influencer, resulting in pK a values in the same range as modelled for the wildtype in absence of an influencer.…”
Section: Apparent Pk a Values From Activity-ph Profilesmentioning
confidence: 77%
“…[ 22 , 23 , 53 , 55 ] More precisely, for pistol, the nature of the cationic influencer can be associated most likely with the electrostatic potential of the “second” hydrated Mg 2+ ion that is located near G40, observed in all crystal structures of precatalytic, transition state mimic, and product states. [33] At this point we mention that also several computational studies shed light on the possible influencer activities,[ 56 , 57 , 58 ] one of them especially points out that the Hoogsteen edge of G40 is exposed to solvent in an electronegative pocket, making the O6 position available to (transiently) interact with metal ions (considerably more than other guanine residues) and that this can tune the p K a at the N1 position. [56] In another computational study, the interesting finding was made (by means of classical MD simulations and QM/MM hybrid calculations) that only the model where the protonation of the nucleotide base was according to the canonical state renders reactive conformations of the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another computational study, the interesting finding was made (by means of classical MD simulations and QM/MM hybrid calculations) that only the model where the protonation of the nucleotide base was according to the canonical state renders reactive conformations of the active site [57] . This was not the case for the models in which guanine G40 was parametrized as deprotonated at the N1 atom (“reversed protonation”) [58] …”
Section: Resultsmentioning
confidence: 99%
“…A recent computational study has reported the possibility of specific base mechanism, as they observed better inline fitness when G40 was protonated and hydrogen bonded to O2′. 37 Proton abstraction by solvent has been proposed for ribozymes before, 38 and discussed as a viable mechanism for the HDV ribozyme 39 where the active site lacks a guanine positioned to act as the base. While a specific base mechanism in Psr can, as yet, not defintively be excluded, as discussed below the current body of evolutionary and functional data suggest the strong possibility that one or more guanine residues play a role in general base catalysis.…”
Section: Rna Cleavage Catalyzed By the Pistol Ribozymementioning
confidence: 99%